2004
DOI: 10.1289/ehp.7027
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Epithelial Integrity in Children: Relationship to Ambient Ozone Exposure and Swimming Pool Attendance

Abstract: Airway irritants such as ozone are known to impair lung function and induce airway inflammation. Clara cell protein (CC16) is a small anti-inflammatory protein secreted by the nonciliated bronchiolar Clara cells. CC16 in serum has been proposed as a noninvasive and sensitive marker of lung epithelial injury. In this study, we used lung function and serum CC16 concentration to examine the pulmonary responses to ambient O3 exposure and swimming pool attendance. The measurements were made on 57 children 10–11 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
2
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 26 publications
7
77
2
4
Order By: Relevance
“…CC16 was also positively associated with cumulated pool attendance, but no clear dose-effect relationship emerged. On the other hand, Lagerkvist et al 41 reported that repeated exposure to chlorination by-products was associated with lower levels of CC16. To explain these contradictory results, it has been suggested that CC16 serum levels reflect both epithelial permeability and Clara cell damage 41 .…”
Section: Respiratory Effects Of Chronic Chlorine Exposure In Nonasthmmentioning
confidence: 99%
See 1 more Smart Citation
“…CC16 was also positively associated with cumulated pool attendance, but no clear dose-effect relationship emerged. On the other hand, Lagerkvist et al 41 reported that repeated exposure to chlorination by-products was associated with lower levels of CC16. To explain these contradictory results, it has been suggested that CC16 serum levels reflect both epithelial permeability and Clara cell damage 41 .…”
Section: Respiratory Effects Of Chronic Chlorine Exposure In Nonasthmmentioning
confidence: 99%
“…On the other hand, Lagerkvist et al 41 reported that repeated exposure to chlorination by-products was associated with lower levels of CC16. To explain these contradictory results, it has been suggested that CC16 serum levels reflect both epithelial permeability and Clara cell damage 41 . In their study, Bernard et al 1 also described a correlation between lung hyperpermeability and total IgE levels, as well as an association between asthma prevalence and cumulated pool attendance.…”
Section: Respiratory Effects Of Chronic Chlorine Exposure In Nonasthmmentioning
confidence: 99%
“…However, some studies have instead linked the increase of CC16 in serum and urine to high intensity training, generating higher permeability in the lung epithelium, thereby enabling leakage to the blood stream [59,61]. When CC16 was measured in children regularly attending swimming pool facilities, not necessarily under intense training, the levels were instead lowered [62]. One in vitro study showed higher release of interleukin 6 (IL-6) and interleukin 8 (IL-8) from human lung cells exposed to swimming pool air, as compared to cells stimulated with trichloramine alone.…”
Section: Swimming Pool Facilitiesmentioning
confidence: 99%
“…Larsson showed that cold air inhalation increased the number of inflammatory cells in broncho alveaveolar lavage (17). In children, Bernard et al found a relationship between the time spent in swimming pools during early childhood and the development of asthma as well as signs of lung involvement by increased serum levels of surfactant proteins (18) and reduced levels of Clara cell protein (19). Also, respiratory tract infections increase bronchial responsiveness in actively training athletes (20).…”
Section: The Environmentmentioning
confidence: 99%